Interest rate on consumer loans and collection of the value added tax in Peru - Sánchez Barraza, Bernardo Javier (2023)
Objective: Determine the correlation between the interest rate on consumer loans and the collection of the Value Added Tax in Peru during the period 2011-2022. Methods: The research was descriptive and correlational in nature. To measure the relationship between the variables, the Spearman correlation coefficient was used, which is suitable for data that do not meet the normality conditions. A total of 144 monthly observations were analyzed, obtained from the Superintendence of Banking, Insurance and Pension Fund Administrators and the National Superintendency of Customs and Tax Administration. Results: There is a positive correlation between the interest rate on consumer loans and the collection of the value added tax in the period from January 2011 to December 2022. Conclusion: When the interest rate on consumer loans increases, so does the collection of the Value Added Tax. However, the relationship between these variables is not constant and may be subject to changes at different times.